Ophthalmic artery Doppler in combination with other biomarkers in prediction of pre‐eclampsia at 35–37 weeks' gestation. (15th March 2021) - Sarno, M.; Wright, A.; Vieira, N.; Sapantzoglou, I.; Charakida, M.; Nicolaides, K. H.
ABSTRACT: Objective: To examine the potential value of maternal ophthalmic artery Doppler at 35–37 weeks' gestation in combination with the established biomarkers of pre‐eclampsia (PE), including mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI), serum placental growth factor (PlGF) and serum soluble fms‐like tyrosine kinase‐1 (sFlt‐1), in the prediction of subsequent development of PE. Methods: This was a prospective observational study in women attending for a routine hospital visit at 35 + 0 to 36 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ultrasound examination for fetal anatomy and growth, assessment of flow velocity waveforms from the maternal ophthalmic arteries, and measurement of MAP, UtA‐PI, serum PlGF and serum sFlt‐1. The competing‐risks model was used to estimate the individual patient‐specific risks of delivery with PE at any time and at < 3 weeks after assessment by a combination of maternal demographic characteristics and medical history with biomarkers. The area under the receiver‐operating‐characteristics curve and detection rate (DR) of delivery with PE, at a 10% false‐positive rate (FPR), in screening by combinations of maternal factors with ophthalmic artery second to first peak of systolic velocity ratio (PSV ratio), MAP, UtA‐PI, serum PlGF and serum sFlt‐1 were determined. The modeled performance of screening for PE was also estimated. Results: The study population of 2287 pregnancies contained 60 (2.6%) that developed PE, including 19 (0.8%) that delivered with PE at < 3 weeks after assessment. The PSV ratio improved the prediction of PE with delivery at any stage after assessment provided by maternal factors alone (from 25.4% to 50.6%), maternal factors and MAP (54.3% to 62.7%), maternal factors, MAP and PlGF (68.3% to 70.8%) and maternal factors, MAP, PlGF and sFlt‐1 (75.7% to 76.7%), at a FPR of 10%. The PSV ratio also improved the prediction of PE with delivery at < 3 weeks after assessment provided by maternal factors alone (from 31.0% to 69.4%), maternal factors and MAP (74.1% to 83.4%), maternal factors, MAP and UtA‐PI (77.1% to 85.0%) and maternal factors, MAP and PlGF (84.8% to 88.6%). The empirical results for DR at a 10% FPR were consistent with the modeled results. Screening by a combination of maternal factors with MAP and PSV ratio also detected 59.4% (95% CI, 58.6–82.5%) of cases of gestational hypertension with delivery at any stage after assessment, and 86.7% (95% CI, 82.4–100%) of those with delivery at < 3 weeks after assessment. Conclusion: Ophthalmic artery Doppler could potentially improve the performance of screening for PE at 35–37 weeks, especially imminent PE with delivery within 3 weeks after assessment, but further studies are needed to validate this finding. © 2020 International Society of Ultrasound in Obstetrics and Gynecology